PERCEPTION, AWARENESS AND KNOWLEDGE OF MENOPAUSAL TRANSITION IN MALAYSIA - MN, Raha; F, Amini; MS, Seghayat (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Perimenopause starts several years before the actual menopause and it is a difficult coping time in women’s life. The fluctuating hormonal level causes physical, physiological and psychological changes in a woman. These symptoms coupled with socioeconomic factors may negatively affect the quality of life. Knowledge of perimenopause and menopause, symptoms management and positive perception may improve health, comfort and happiness. This study aims to find out the level of knowledge and awareness of menopause and its management, beside prevalence of menopausal symptoms in a perimenopausal group of women. METHODOLOGY A cross-sectional study was conducted. Self-administered questionnaires were distributed and retrieved from perimenopausal women aged 40 to 51 years old. They were enrolled during clinic visits in the General Practitioner clinic. RESULT A total of 182 participants were recruited. Majority were Malay (77%), had secondary school education (36.3%), and were married (85.7%). Only 47.8% had normal BMI. The mean knowledge score was 11.60±3.63. 54% had good knowledge on definition of menopause and menopausal symptoms management. A significant association was observed between level of knowledge and marital status, (p=0.002), educational background (p=0.038), and number of children (p=0.02). Perimenopausal symptoms were prevalent, notably the musculoskeletal symptoms, lack of energy, sleep disturbances and mood swing. However, there was poor awareness in attributing these symptoms to perimenopause despite the high incidence reported. Only a mere 14.8% were aware of methods to help ease symptoms. Women of perimenopausal age perceive menopause more positively compared to younger women. CONCLUSION This study suggests that about half of participants had poor level of knowledge about perimenopause. Harnessing this knowledge will likely influence their health and treatment seeking behaviour. A concerted effort by media, magazines, educational programmes and active discussion with the health providers are invaluable.